Detection of Rotor Forced Response Vibrations Using Stationary Pressure Transducers in a Multistage Axial Compressor - William L. Murray; Nicole L. Key (International Journal of Rotating Machinery)
Blade row interactions in turbomachinery can lead to blade vibrations and even high cycle fatigue. Forced response conditions occur when a forcing function (such as impingement of stator wakes) occurs at a frequency that matches the natural frequency of a blade. The objective of this research is to develop the data processing techniques needed to detect rotor blade vibration in a forced response condition from stationary fast-response pressure transducers to allow for detection of rotor vibration from transient data and lead to techniques for vibration monitoring in gas turbines. This paper marks the first time in the open literature that engine-order resonant response of an embedded bladed disk in a 3-stage intermediate-speed axial compressor was detected using stationary pressure transducers. Experiments were performed in a stage axial research compressor focusing on the embedded rotor of blisk construction. Fourier waterfall graphs from a laser tip timing system were used to detect the vibrations after applying signal processing methods to uncover these pressure waves associated with blade vibration. Individual blade response was investigated using cross covariance to compare blade passage pressure signatures through resonance. Both methods agree with NSMS data that provide a measure of the exact compressor speeds at which individual blades enter resonance.